2019
DOI: 10.1136/bmjresp-2019-000420
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the management of acute respiratory distress syndrome

Abstract: The Faculty of Intensive Care Medicine and Intensive Care Society Guideline Development Group have used GRADE methodology to make the following recommendations for the management of adult patients with acute respiratory distress syndrome (ARDS). The British Thoracic Society supports the recommendations in this guideline. Where mechanical ventilation is required, the use of low tidal volumes (<6 ml/kg ideal body weight) and airway pressures (plateau pressure <30 cmH2O) was recommended. For patients with moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
374
0
42

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(419 citation statements)
references
References 139 publications
(202 reference statements)
3
374
0
42
Order By: Relevance
“…U.S., European Union, and recently released United Kingdom ARDS guidelines strongly recommend the use of low tidal volume ventilation (4 to 8 ml/kg predicted body weight in the U.S./European Union guidelines or less than 6 ml/kg in the United Kingdom guidelines, to maintain plateau pressures less than 30 cm H 2 0), with permissive hypercapnia. 77,78 The U.S., European Union, and United Kingdom guidelines also strongly recommend the use of prone positioning for greater than 12 h per day in patients with severe (moderate-severe in United Kingdom guidelines) ARDS, and this recommendation is echoed in the World Health Organization SARS-CoV-2 guideline. 77,78 However, as prone ventilation is a resource-intensive intervention where the endotracheal tube and other lines may become displaced, it is only recommended when there are sufficient human resources and expertise within the medical center for this intervention to be performed safely.…”
Section: Management Of Covid-19-associated Respiratory Failurementioning
confidence: 99%
See 1 more Smart Citation
“…U.S., European Union, and recently released United Kingdom ARDS guidelines strongly recommend the use of low tidal volume ventilation (4 to 8 ml/kg predicted body weight in the U.S./European Union guidelines or less than 6 ml/kg in the United Kingdom guidelines, to maintain plateau pressures less than 30 cm H 2 0), with permissive hypercapnia. 77,78 The U.S., European Union, and United Kingdom guidelines also strongly recommend the use of prone positioning for greater than 12 h per day in patients with severe (moderate-severe in United Kingdom guidelines) ARDS, and this recommendation is echoed in the World Health Organization SARS-CoV-2 guideline. 77,78 However, as prone ventilation is a resource-intensive intervention where the endotracheal tube and other lines may become displaced, it is only recommended when there are sufficient human resources and expertise within the medical center for this intervention to be performed safely.…”
Section: Management Of Covid-19-associated Respiratory Failurementioning
confidence: 99%
“…77,78 The U.S., European Union, and United Kingdom guidelines also strongly recommend the use of prone positioning for greater than 12 h per day in patients with severe (moderate-severe in United Kingdom guidelines) ARDS, and this recommendation is echoed in the World Health Organization SARS-CoV-2 guideline. 77,78 However, as prone ventilation is a resource-intensive intervention where the endotracheal tube and other lines may become displaced, it is only recommended when there are sufficient human resources and expertise within the medical center for this intervention to be performed safely. 49 The World Health Organization guidelines for the management of COVID-19 echo the United Kingdom ARDS guidelines in recommending a conservative fluid management strategy for patients without evidence of tissue hypoperfusion.…”
Section: Management Of Covid-19-associated Respiratory Failurementioning
confidence: 99%
“…Since the three randomized controlled trials on the effects of neuromuscular blocker totaling 431 showed survival benefits dating back before 2010, the clinical guidelines have recommended NMBA as supportive treatment of severe ARDS. The recommendation strength was only weak to moderate due to the lack of blinding and the risk of indirectness in the contributing studies [6,8,31]. There are also still concerns about ICU-related weakness and other risks associated with NMBA, such as atelectasis, diaphragm paralysis, and anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In a large observational study, the mortality rate of moderate to severe ARDS was up to 40% [4]. Neuromuscular blocking agents (NMBA) have been proposed during the early course of moderate to severe ARDS especially in those with PaO 2 /FIO 2 < 120 mmHg to improve oxygenation and reduce patient-ventilator dyssynchrony [6][7][8]. NMBA facilitates oxygenation in various studies [9][10][11] by various mechanisms, including reducing ventilator-induced lung injuries and inhibiting inflammatory cytokines [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Multiple studies have been conducted on simulation lungs or animals, but none attempted to simultaneously individualize tidal volume and positive end expiratory pressure (PEEP) in lungs of varying compliancesmainstays of treatment therapy in severe acute respiratory distress syndrome (ARDS). [9][10][11][12][13] Our findings suggest that multiple patients of different compliances can be successfully ventilated from a single source with individually tailored tidal volumes and PEEP. To our knowledge, this is the first journal publication to demonstrate this.…”
Section: Covid-19mentioning
confidence: 99%